Aplicación web para la comercialización de productos en la farmacia “santo remedio” usando la metodología de desarrollo Microsoft Solution Framework - Intriago Granda, José Ignacio (2023)
The marketing of products worldwide, has reached competitive standards due to the use of technologies that have improved the process of buying and selling products, thus forcing all sectors to constantly update to sell their products. In this research project a web application was developed to improve the marketing of products in the pharmacy "Santo Remedio". The Microsoft Solution Framework methodology was considered for the development of the software, which provides a complete and flexible guide on the phases of: vision, planning, development, release, stabilization, the Php language was used, the PhpMyAdmin database, the usability was verified by the principles of Jakob Nielsen. The research concludes that the Microsoft Solution Framework (MSF) methodology improves software project management. By implementing MSF in the web application of the "Santo Remedio" pharmacy, it was possible to meet objectives and deliver a quality solution. The usability evaluation confirmed compliance with Jakob Nielsen's principles